Psychological Capital and Academic Burnout among Students in Islamic Boarding Schools: The Mediating Effects of Religious Coping and Academic Engagement - Ahmad, Bukhari; Sujadi, Eko (citeus, 2026)
This study aims to examine the impact of psychological capital on academic burnout among Islamic boarding school students, with religious coping and academic engagement as mediating variables. A quantitative research method with survey design was employed. The population consisted of 102 students at the Madrasah Tsanawiyah level, and a sample of 80 students was determined using the Krejcie and Morgan formula. The sampling technique used was simple random sampling. Four validated research scales were adapted for data collection: the Oldenburg Burnout Inventory – Student Version (OLBI-S), Compound Psychological Capital Scale (PsyCap-12), The Brief RCOPE, and the Utrecht Work Engagement Scale for Students (UWES-9S). Hypotheses were tested using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results indicate that psychological capital, religious coping, and academic engagement significantly and directly affect academic burnout. Moreover, religious coping and academic engagement serve as significant mediators in the relationship between psychological capital and academic burnout. These findings provide valuable insights for administrators of Islamic boarding schools and similar educational institutions. Interventions aimed at developing psychological resilience, enhancing academic engagement, and strengthening spirituality are recommended as effective strategies to mitigate academic burnout.